Creativity In Persuasive Communication y The Mosque Prosperity Council: Building Public Trust For The Ghairu Mahdha Worship Program At Usuwatun Hasanah Grand Mosque - Firdha Nurbaiti; Rosmawaty Hilderiah Pandjaitan; Afdal Makkuraga Putra (INJECT (Interdisciplinary Journal of Communication), 2025)
Building public trust to participate in a social program with a religious nuance that does not provide direct financial benefits is not simple. This study aims to describe the forms and obstacles to the creativity of persuasive communication of the Mosque Prosperity Council (DKM) in implementing the Ghairu Mahdha Worship Program at the Usuwatun Hasanah Grand Mosque. The study used a qualitative approach with a case study method and a constructivist paradigm. Data collection techniques were carried out through semi-structured, in-depth interviews. The theories used as analysis tools are relationship maintenance theory, adaptation interaction theory, and computer-mediated communication theory. The results of the study showed that DKM succeeded in building persuasive communication through transparency of fund reports during Friday sermons, an inclusive attitude towards all congregations, and active community involvement in program planning. Ghairu Mahdha worship programs, such as free circumcision, free marriage, dawn vegetable harvest, and Monday-Thursday iftar, are designed in a participatory manner and based on the values ​​of the Qur'an, especially Surah At-Taubah verse 18. DKM also transforms the function of the mosque from a mahdhah place of worship to a center for community solutions, inspired by mosques in Java Jogokariyan. Communication is carried out directly and indirectly through social media and live streaming. The main obstacle found was the lack of education during the change of management, which had an impact on the continuity of the program. This study contributes to the study of socio-religious communication and can be a practical reference for other mosques.